Critical Discourse Analysis of Novel "Yusuf dan Mentari" by Irma Surya - Goziyah Goziyah; Shazha Nurul Asifa (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
This study aims to describe a form of discourse analysis based on discourse and text describing the factors that affect the practice of discourse. The goal prompted researchers to examine in a study entitled "Critical Discourse Analysis on “Novel Yusuf and Mentari” by Irma Surya”. The method used in this research is descriptive qualitative. The results showed that: first, the critical discourse analysis see representation or description text displayed events ranging from active to bring perpetrators sentences and semantically interpret deskridtif, describes between one clause with the clause can be combined so that they form a sentence meaning or the sense of coherence or cohesion. Keywords: critical discourse analysis, discourse practices, novel, representation, sociocultural Abstrak Penelitian ini bertujuan untuk mendeskripsikan bentuk analisis wacana berbasis wacana dan teks. Tujuan penelitian ini adalah menelaah dan mendeskripsikan faktor yang mempengaruhi praktik wacana dalam penelitian yang berjudul “Analisis Wacana Kritis pada Novel Yusuf dan Mentari Karya Irma Surya”. Metode penelitian ini adalah deskriptif kualitatif. Hasil penelitian menghasilkan analisis wacana kritis representasi atau teks deskripsi peristiwa yang ditampilkan mulai dari aktif hingga membawakan kalimat pelaku dan menafsirkan deskripstif secara semantik serta menjelaskan antara satu klausa dengan klausa lainnya dapat digabungkan sehingga membentuk sebuah kalimat atau rasa koherensi atau kohesi. Kata kunci: analisis wacana kritis, praktik wacana, novel, representasi, sosiokultural